Editorial: post‐operative complications in elderly onset inflammatory bowel disease—what is surgery, what is disease, and what is delay of surgery? Authors' reply. Issue 3 (11th July 2018) - Savoye, G.; Fumery, M.; Gower‐Rousseau, C.
Abstract : Linked Content This article is linked to Sacleux et al and Myrelid papers. To view these articles visit https://doi.org/10.1111/apt.14790 and https://doi.org/10.1111/apt.14833 .